What makes a good mentor of in-service teacher education? —A systematic review of mentoring competence from a transformative learning perspective - Wang, Xuewei; Husu, Jukka; Toom, Auli (Elsevier BV, 2025)
Previous research has explored what competence qualified mentors need to possess. However, with the increasing advocacy that mentoring can be a professional learning experience for mentors, no studies have synthesized mentoring competence reflected in their mentoring practice. By using the framework of transformative learning theory, this study systematically synthesized 56 empirical studies on in-service teacher mentoring published between 2015 and 2022. The findings provide a conceptual framework for mentoring competence in three dimensions (cognitive, social, and emotional) with eight categories and summarize mentor- and context-related influencing factors. These findings suggest theoretical and practical implications for advancing the research of teacher mentoring.